Translocar: Por un Pensamiento Situado en Movimiento - Vallim de Melo, Aline (Corpo Grafías Estudios críticos de y desde los cuerpos, 2025)
This article, derived from the results of my doctoral thesis, co-directed by Dr. Maria Teresa Garcia (UDFJC) and Dr. Monique Martínez (UT2J), explores possible intersections between dance, gender and migration based on the bodily experiences and life stories of migrant women from different contexts. Inserted in the field of Artistic Studies, the investigation starts from the understanding that migrant bodies carry memories, resistances and knowledge that challenge geographical boundaries and stereotypical social representations about being a woman. Given the historical invisibility of female experiences, the study seeks to understand how dance practices can act as tools for political expression and identity construction. In this sense, Translocar proposes a methodological path that seeks to make visible skills and devices in dance that can expand the ways of problematizing and valuing the life experiences of migrant women, with the horizon of transforming vulnerabilities historically associated at them.